Efficiency of insect‐proof net tunnels in reducing virus‐related seed degeneration in sweet potato - Ogero, K.; Kreuze, Jan F.; McEwan, M.; Luambano, N.D.; Bachwenkizi, H.; Garrett, K.A.; Andersen, K.F.; Thomas-Sharma, Sara; Vlugt, R.A.A. (Wiley, 2019)
Virus‐related degeneration constrains production of quality sweet potato seed, especially under open field conditions. Once in the open, virus‐indexed seed is prone to virus infection leading to decline in performance. Insect‐proof net tunnels have been proven to reduce virus infection under researcher management. However, their effectiveness under farmer‐multiplier management is not known. This study investigated the ability of net tunnels to reduce degeneration in sweet potato under farmer‐multiplier management. Infection and degeneration were assessed for two cultivars, Kabode and Polista, grown in net tunnels and open fields at two sites with varying virus pressures. There was zero virus incidence at both sites during the first five generations. Sweet potato feathery mottle virus and sweet potato chlorotic stunt virus were present in the last three generations, occurring singly or in combination to form sweet potato virus disease. Virus infection increased successively, with higher incidences recorded at the high virus pressure site. Seed degeneration modelling illustrated that for both varieties, degeneration was reduced by the maintenance of vines under net tunnel conditions. The time series of likely degeneration based on a generic model of yield loss suggested that, under the conditions experienced during the experimental period, infection and losses within the net tunnels would be limited. By comparison, in the open field most of the yield could be lost after a small number of generations without the input of seed with lower disease incidence. Adopting the technology at the farmer‐multiplier level can increase availability of clean seed, particularly in high virus pressure areas.